Proceedings of the 2014 ACM Symposium on Principles of Distributed Computing 2014
DOI: 10.1145/2611462.2611486
|View full text |Cite
|
Sign up to set email alerts
|

The amortized complexity of non-blocking binary search trees

Abstract: We improve upon an existing non-blocking implementation of a binary search tree from single-word compare-and-swap instructions. We show that the worst-case amortized step complexity of performing a Find, Insert or Delete operation op on the tree is O(h(op) +ċ(op)) where h(op) is the height of the tree at the beginning of op andċ(op) is the maximum number of operations accessing the tree at any one time during op. This is the first bound on the complexity of a non-blocking implementation of a search tree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
1
36
0
Order By: Relevance
“…For example, in the concurrent computing world, Ellen et al [19] show how to design a non-blocking binary search tree, with later work generalizing this technique [13] and analyzing the amortized complexity [18]. However, these data structures do not maintain balance in the tree (i.e., the height can get large) and their cost depends on the number of concurrent operations.…”
Section: Parallel Search Structuresmentioning
confidence: 99%
“…For example, in the concurrent computing world, Ellen et al [19] show how to design a non-blocking binary search tree, with later work generalizing this technique [13] and analyzing the amortized complexity [18]. However, these data structures do not maintain balance in the tree (i.e., the height can get large) and their cost depends on the number of concurrent operations.…”
Section: Parallel Search Structuresmentioning
confidence: 99%
“…Specifically, before a record is removed from the data structure, it is marked, and no process is allowed to change a marked node. Search operations can often traverse marked nodes, and even leave the data structure to traverse some retired nodes, and still succeed (see, e.g., [4,7,8,13,16,15,21,23,30,31,33]).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, for some data structures, the amortized cost of operations depends on the number of marked nodes they traverse. Searching again from an entry point can provably lead to an asymptotic increase in the amortized cost of operations [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been increased interest in the analytical properties of lock-free data structures [1,9,16]. Herlihy and Shavit [16] suggested that, on realistic schedules, lock-free algorithms ensure that each operation completes in a finite number of its own steps, i.e., that lock-free algorithms are in fact wait-free [13].…”
Section: Introductionmentioning
confidence: 99%